197 Leading through education through excellent patient care (LEEP) – leadership development programme. (16th November 2020) - Sait, Saif; Manea, Cristina; May, Hannah; Szram, Jo; Nayar, Vijay; Menon, Geeta
Abstract : Aims: Practical leadership skills have never been more important in healthcare professionals than over the last year, during the global COVID-19 pandemic. In response we transformed a four-day face to face programme – Leading through Education to Excellent Patient Care (LEEP) into a webinar/workshop series. These focus on four perspectives: developing as an individual, developing your team, working in a network to improve change, and developing system literacy. He we share our experience of the first webinar delivery focused on 'developing self' Methods: We ran the first webinar for foundation year one doctors on three occasions. The webinar was integrated within a flipped classroom approach, with pre-webinar learning, and webinars consisting of small group discussion and mini lectures. Results: Forty-eight participants attended; following the course, participants stated that they had greater understanding in the purpose of leadership in healthcare was and understood more about their own strengths and weaknesses in being a leader. Attendees found that their confidence increased in all 11 topics when compared to pre-course (scale 1–10), covered including (pre to post course): leadership styles (5.5/10 to 8.5/10), compassionate leadership (5.6/10 to 8.8/10) and Johari window (3/10 to 8.5/10). Some comments from the course were 'I felt encouraged to participate and join in as it was very interactive' and 'I came away feeling genuinely inspired'. 97% of participants who attended the webinar said they would recommend this course to others. Conclusion: This novel virtual leadership development course was well received and led to globally improved confidence in understanding through a blending approach of flipped learning, mini-lectures, reflection, and interactive discussion. We aim to continue the course by holding a further virtual workshops/webinar for foundation year 1 doctors, as well as developing them for delivery to other healthcare professionals.